A biomechanical study of proximal tibia bone grafting through the lateral approach. Issue 11 (November 2016) - Lim, Chin Tat; Ng, David Q.K.; Tan, Ken Jin; Ramruttun, Amit K.; Wang, Wilson; Chong, Desmond Y.R.
Abstract: Background: Autologous bone graft remains the gold standard source of bone graft. Iliac crest has traditionally been the most popular source for autologous bone graft. However, iliac crest bone graft harvesting is associated with high donor site morbidity. Bone graft harvesting from the proximal tibia has shown great potential with reported low complication rates. However, there is a paucity of biomechanical studies concerning the safety as well as yield of proximal bone graft harvesting. Purpose: This biomechanical study was designed to investigate (1) the stability of the harvested proximal tibial during physiological loading, and (2) the maximum size of the cortical window that can be safely created and (3) volume of accessible bone graft. Methods: Bone grafts were harvested from eleven cadaveric tibiae using a circular cortical window along the lateral proximal tibia. These harvested proximal tibiae were then loaded under physiological conditions (mean 2320N, range 1650–3120N) using a customized test fixture. Strain rosettes were mounted at 7 locations in the harvested proximal tibia to record the changes in strain at the harvested proximal tibia. The change in strain with increasing cortical window size (10–25 mm diameter) was also studied. Bone principal strains as well as volume of bone harvested were recorded. Results: A repeated measures ANOVA was used to analyze the change in bone strains with the cortical window size. Statistically significant (p < 0.05) increases in bone strains at the anterior and medial aspects of the tibia were observed with increasing size of osteotomies (−328.85 με, SD = 232.21 to −964.78 με, SD = 535.89 and 361.64 με, SD = 229.90 to −486.08 με, SD = 270.40 respectively), and marginally significant changes in strain at the lateral and posterior aspects. None of the tibiae failed under normal walking loads even with increasing osteotomies size of 10–25 mm diameter. A smaller osteotomy of 10 mm diameter yielded an average volume of 7.15 ml of compressed bone graft, while a larger osteotomy of 25 mm diameter yielded on average an additional 3.64 ml of bone graft. Bone grafting of the proximal tibia through the lateral approach with a circular osteotomy is a feasible option even with osteotomies of 25 mm diameter. Even though increased bone strains were observed, the strains did not exceed the yield strain of cortical bone when loaded under normal walking conditions. The quantity of bone harvested from the proximal tibia is comparable to that harvested from the iliac crest. Conclusions: This biomechanical study demonstrated the stability of the harvested proximal tibia under conditions of full weight bearing ambulation. It has also refined the technique of proximal bone graft harvesting by determining the maximum size of the cortical window. The findings of this study add to the overall understanding of proximal tibial bone graft harvesting, providing objective data regarding stability as well as yield. This information would be useful during selection of source of autologous bone graft.